Effectiveness and cost-effectiveness of an exposure-based return-to-work programme for patients on sick leave due to common mental disorders: design of a cluster-randomized controlled trial - Nieuwenhuijsen Karen; van Dijk Frank J; Noordik Erik; van der Klink Jac JL (BMC, 2009)
Abstract Background To reduce the duration of sick leave and loss of productivity due to common mental disorders (CMDs), we developed a return-to-work programme to be provided by occupational physicians (OPs) based on the principles of exposure in vivo (RTW-E programme). This study evaluates this programme's effectiveness and cost-effectiveness by comparing it with care as usual (CAU). The three research questions we have are: 1) Is an RTW-E programme more effective in reducing the sick leave of employees with common mental disorders, compared with care as usual? 2) Is an RTW-E programme more effective in reducing sick leave for employees with anxiety disorders compared with employees with other common mental disorders? 3) From a societal perspective, is an RTW-E programme cost-effective compared with care as usual? Methods/design This study was designed as a pragmatic cluster-randomized controlled trial with a one-year follow-up and randomization on the level of OPs. We aimed for 60 OPs in order to include 200 patients. Patients in the intervention group received the RTW-E programme. Patients in the control group received care as usual. Eligible patients had been on sick leave due to common mental disorders for at least two weeks and no longer than eight weeks. As primary outcome measures, we calculated the time until full return to work and the duration of sick leave. Secondary outcome measures were time until partial return to work, prevalence rate of sick leave at 3, 6, 9, and 12 months' follow-up, and scores of symptoms of distress, anxiety, depression, somatization, and fatigue; work capacity; perceived working conditions; self-efficacy for return to work; coping behaviour; avoidance behaviour; patient satisfaction; and work adaptations. As process measures, we used indices of compliance with the intervention in the intervention group and employee-supervisor communication in both groups. Economic costs were calculated from a societal perspective. The total costs consisted of the costs of consuming health care, costs of production loss due to sick leave and reduced productivity, and out-of-pocket costs of patients for travelling to their OP. Discussion The results will be published in 2009. The strengths and weaknesses of the study protocol are discussed. Trial registration ISRCTN72643128